The Impact of Glucose-6-Phosphate Dehydrogenase Deficiency on the Frequency of Vasoocclusive Crisis in Patients with Sickle Cell Anemia. (September 2021) - Nnamezie Igwilo, Hilary; Salawu, Lateef; Adeoye Adedeji, Tewogbade
Background and Objectives: Sickle cell anemia (SCA) and glucose-6-phosphate dehydrogenase (G6PD) deficiency are both hereditary diseases of the red blood cells that cause hemolysis. The impact of the interaction of both conditions on the clinical and laboratory presentations of the affected persons is sparse. This study, therefore, correlated G6PD activity with disease severity in persons with SCA by comparing disease severity in G6PD-deficient SCA persons with those with normal G6PD activity. Methodology: This cross-sectional study was conducted in the department of Haematology and Blood Transfusion of the Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. G6PD activity, SCA disease severity, and hematological parameters including reticulocyte counts and Heinz body estimation, bilirubin, and aspartate transaminase were estimated in 67 SCA persons. The results were compared between SCA persons with G6PD deficiency and those with normal enzyme activity. Results: The prevalence of G6PD deficiency was found to be 23.9%. The G6PD-deficient SCA patients included 4 (25.0%) males and 12 (75.0%) females. G6PD deficiency was significantly higher in females ( P = .047). There was no significant difference in disease severity scores between G6PD-deficient and G6PD-nondeficient SCA patients. However, G6PD-deficient persons reported significantly higher episodes of severe vasoocclusive crisis (VOC) per annum ( P = .048). The hematological and biochemical parameters were similar between G6PD-deficient and G6PD normal SCA persons except that the G6PD-deficient SCA persons have significantly higher reticulocyte response ( P = .001). There was no correlation between disease severity resulting from reduced G6PD activity and Heinz body formation in SCA persons in the steady state. Conclusion: G6PD deficiency significantly contributes to recurrent painful vasoocclusive crisis in SCA persons in the steady state.